KEWENANGAN PERADILAN TATA USAHA NEGARA TERHADAP PEMBATALAN SERTIFIKAT HAK ATAS TANAH YANG DITERBITKAN SEBELUM DIUNDANGKANNYA UNDANG-UNDANG NO 5 TAHUN 1986 (ANALISIS KASUS: PUTUSAN MAHKAMAH AGUNG NO. 458/K/TUN/2017) - Muhammad apriodi effendy; Rasji Rasji (Jurnal Hukum Adigama, 2021)
The State Administrative Court is one of the executors of judicial power for people who seek justice for state administrative disputes, the State Administrative Court is regulated in Law Number 5 of 1986, which becomes the object of the State Administrative Court is a written decision by a state administrative official (beschikking). that is, a written stipulation issued by a State Administrative Body or Official that contains a State Administrative Law action based on the prevailing laws and regulations which are concrete, individual and final in nature which give rise to legal consequences for a person or a Civil Legal Entity. This thesis research uses a qualitative approach and descriptive type. Land title certificate is one of the objects of the State Administrative Court but the UUPTUN does not clearly regulate the land title certificate issued before the enactment of the UUPTUN is an object of the State Administrative Court or not so it is necessary to have rules that clearly regulate this problem so that it can create certainty law.